A model for teletraffic performance and channel holding time characterization in wireless cellular communication with general session and dwell time distributions. - Orlik, P.V (IEEE Journal on selected areas in communications)
Channel holding times and user mobility are important topics in the study of wireless cellular communications. We present an approach to modeling user mobility and session time which enables both the calculation of teletraffic performance characteristics and a characterization of holding time which agrees with published reports. The model allows both the dwell time and unencumbered session time to have general distributions. A derivation of the channel holding time distribution is given. We then show how the model's parameters can be chosen to fit empirical data including observations of channel holding time